Pengaruh Kualitas Produk dan Harga terhadap Kepuasan Konsumen Di Z’Coffee - Siti Ila Sulaila; Tiara Cahyani; Muhammad Ipan (Yayasan Literasi Sains Indonesia, 2025)
This research aims to examine the effect of product quality and price on customer satisfaction at Z’Coffee, a growing coffee shop in Bogor City. A quantitative research method was employed, using a questionnaire distributed to 52 customers. The collected data were analyzed using multiple linear regression along with classical assumption tests to validate the model. The findings reveal that product quality has a significant and positive impact on customer satisfaction. In contrast, price does not show a significant effect when tested partially. However, when tested simultaneously, both product quality and price significantly influence customer satisfaction, with a coefficient of determination (R²) of 75.4%. This indicates that the model explains 75.4% of the variation in customer satisfaction. The study highlights that product quality plays a more dominant role compared to price in influencing satisfaction. Based on these findings, Z’Coffee is advised to focus on improving product quality in its marketing strategies to enhance customer satisfaction and loyalty, especially in a competitive culinary industry environment.